FAKTOR-FAKTOR YANG MENGHAMBAT PERTUMBUHAN USAHA MIKRO JAJANAN TRADISIONAL DI SURABAYA - Endang Siswati; Juliani Pudjowati (Unitri Press, 2021)
The purpose of this study was to evaluate several factors that hinder business growth, included capital constraints, quality of human resources, marketing capabilities, access to information, and partnerships in Surabaya. Respondents in this study were traditional micro snack entrepreneurs that used purposive sampling instrument like a Likert scale. In this study, the data analysis was used multiple linear regression. The findings in this study were the variables of capital, quality of human resources, marketing ability, access to information, and partnerships did not affect business growth. However, partially the capital variable did not have a significant effect on the growth of micro-businesses, while the variable of marketing ability increases negatively on the growth of micro-businesses, however, consumers can buy directly by visiting the business premises. The variable access to information has a significant and most dominant effect on business growth with a regression coefficient is 1.603 with a significance level of 0.013. The partnership variable has a significant effect on the growth of micro-businesses. In the development of MSME businesses, the presence of partners was very helpful and increased business growth